Analisis Kemampuan Membaca Kelas III SD Negeri 31 Mataram - Aulia, Rizka; Rasma, Rizkia; Kandias, Saidul; Serli, Serli; Astiana, Windi; Witono, Hari; Ibrahim, Ibrahim (Indonesian Publication Center, 2024)
In life, reading has an important role because reading is one of the ways used to increase knowledge. The goal of reading skills is so that students can understand texts and become better communicators. This research was conducted with the aim of analyzing the reading abilities of grade 3 students at SDN 31 Mataram. The research methodology used is descriptive qualitative with data collection techniques through tests, observations and interviews. This research resulted in eight students having good reading abilities, three students having fairly good reading abilities, and one student having very poor reading abilities. Based on the findings from tests, observations, and interviews conducted for this research, three conclusions can be drawn about the reading abilities of grade 3 students at SDN 31 Mataram: some of them are proficient readers. Other students' reading abilities ranged from very poor to sufficient.